Alkoholkonsum und Krebsrisiko - Scherübl, Hans (DMW - Deutsche Medizinische Wochenschrift, 2019)
Alcohol use is one of the most important and potentially modifiable risk factors for cancer in Germany. The more and the longer a person drinks, the higher the risk of cancer. Even modest use of alcohol may increase cancer risk. Statistically, every German drinks more than 100 gram of alcohol per week; this amount is currently considered to be the limit of low-risk use. Alcohol is causally associated with oropharyngeal and larynx cancer, esophageal squamous cell cancer, hepatocellular carcinoma, breast cancer, and colorectal cancer. People with long-term risky alcohol use should be encouraged to join programs of cancer screening. Alcohol cessation appears to be effective in reducing the alcohol-induced, increased cancer risk.
Keywords: Darmkrebs; Kopf-Hals-Tumoren; Brustkrebs; Leberkrebs; Ösophaguskarzinom; präventive Tumormedizin